The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-40422007000600008
|View full text |Cite
|
Sign up to set email alerts
|

Indústria química: evolução recente, problemas e oportunidades

Abstract: CHEMICAL INDUSTRY: RECENT DEVELOPMENTS, PROBLEMS AND OPPORTUNITIES. Chemical industry underwent a significant upturn in the past few years. In Brazil, the position of this industry has been continuously strengthened as the second largest industrial sector. Current circumstances are discussed, especially the need for increased innovation, the impacts of nanotechnology, biotechnology and information technologies. Some misconceptions on the Brazilian chemical industry are criticized and recent improvements are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…Another sector that stands out among academics is the chemical industry, which -in this study -showed average values of capacity to innovate and risk. In turn, different studies, such as those by Galembeck et al (2007) and Avelar & Souza (2005), highlight the main risks suffered by this sector: process infrastructure (leakage of waste in the environment), and pharmaceutical/beauty products that cause side effects or do not meet consumer expectations. Accordingly, the main investments in this sector are aimed at control equipment and new technological processes, aiming to reduce the aforementioned risks.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Another sector that stands out among academics is the chemical industry, which -in this study -showed average values of capacity to innovate and risk. In turn, different studies, such as those by Galembeck et al (2007) and Avelar & Souza (2005), highlight the main risks suffered by this sector: process infrastructure (leakage of waste in the environment), and pharmaceutical/beauty products that cause side effects or do not meet consumer expectations. Accordingly, the main investments in this sector are aimed at control equipment and new technological processes, aiming to reduce the aforementioned risks.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The technical nature of the products requires a greater approximation between suppliers and buyers, in order to explore different customization possibilities (Galembeck et al, 2007). The chemical industry is also characterized by substantial investments in research and development, in its search for technological innovations that enable companies to keep up with the rapid advances in market demands while being able to offer multiple application solutions for portfolio products (Brito, Brito, & Morganti, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Altos investimentos estão sendo feitos hoje nas indústrias, como aquisição de equipamentos, como filtros, sendo muitos com tecnologia de membranas, tratamentos e co-processamento de resíduos gerados, visando assim, menores fatores de riscos ambientais (GALEMBECK et al, 2007).…”
Section: Indústrias Químicasunclassified